Perancangan Notifikasi Pesan Disposisi Pada Sistem Pengelolaan Surat Dinas Menggunakan Layanan API Media Social - Billy Gerardhy Lainsamputty; Suprihadi Suprihadi (AITI, 2019)
Based on the Department of Agriculture which still does not have the tools or media to manage the letter of service, both the incoming and outgoing mail which impact on the weak supervision follow-up of the service letter due to ignorance that the letter should be processed. This study was made as a visual and text notification of incoming and outgoing mail data with more detailed archive storage. This website application is supported by using social media telegram API service that is used as notification in the form of notification to the employee so that the Service Letter can be followed up immediately.